The Influence of the Strictness of Tax Sanctions, the Level of Public Trust in the Government, the Quality of Services, the Level of Awareness, and Subjective Norms on Taxpayer Compliance in Increasing APBN Revenue (Case Study at KPP Pratama South Cikaran - Astria, Yuliana Mega; Wulandari, Siska (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to examine the influence of the strictness of tax sanctions, the level of public trust in the government, service quality, level of awareness, and subjective norms on taxpayer compliance in increasing APBN revenues (case study at KPP Pratama South Cikarang) using a quantitative approach. The sampling technique used was probability sampling with a sample size of 100 taxpayer respondents registered at KPP Pratama Cikarang Selatan. Data collection was carried out through a questionnaire using a Likert scale. The analysis method in this research uses Structural Equation Modeling (SEM) with SmartPLS 4.0.9.5 Software via Google Forms. Testing includes outer model analysis, inner model analysis, and hypothesis testing. The results of the research show that the Firmness of Tax Sanctions has a significant positive influence on Taxpayer Compliance, the Level of Public Trust in the Government has a significant negative influence on Taxpayer Compliance, Service Quality has a positive but not significant influence on Taxpayer Compliance, the Level of Awareness has a significant positive influence on Taxpayer Compliance. Taxpayer Compliance and Subjective Norms have a negative but insignificant influence on Taxpayer Compliance.